WAP: free-for-all. - Biers, Dan (Far Eastern Economic Review, 2000)
The mobile-phone industry in Taiwan is experiencing a battle between operators to roll out services that allow users to access the Internet through wireless application protocol (WAP). This new technology is expected to stop the decline in revenue per user caused by the fight for market share. Analyst Richard Wu of Jardine Fleming says that WAP will cause revenue to stabilize and then increase. However, Wu argues that the companies that launched WAP services early will have an advantage in having more time to prepare for the arrival of general packet radio service later in 2000.